Language, society and power : an introduction - Mooney, Annabelle, 1974-; Evans, Betsy (Betsy Erin) (Routledge, 2019)
"Language, Society and Power is an accessible introduction to studying language in a variety of social contexts. This book examines the ways language functions, how it influences the way we view society and how it varies according to age, ethnicity, class and gender. It considers whether representations of people and their language matter, explores how identity is constructed and performed, and considers the creative potential of language in the media, politics and everyday talk. The fifth edition of this popular textbook features: Updated chapters with new activities; Examples that include material related to youth language, computer-mediated communication, texting and electronic communication; New material on online mass media, fake news and Twitter as a form of political agency; More discussion of social media, social networking, memes and mobile communication; An introduction to the concepts of translanguaging and superdiversity; An expanded Gender chapter that questions binary gender identities; A companion website which includes more video material to support learning as students make their way through the book. Language, Society and Power assumes no linguistic background among readers, and is a must-read for all students of English language and linguistics, media, communication, cultural studies, sociology and psychology who are studying language and society for the first time"--